Digital Disruptions in the Nigerian Postal Industry: NIPOST`s Customers` perception on its Operations in Ughelli, Delta State - Jammy Seigha Guanah; Loveth Okowa-Nwaebi; Oke Edward Edherue; Muhammad Ridwan (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2024)
This paper provided an in-depth analysis of the impact of digital disruption on the Nigerian Postal Industry, with a particular focus on the Nigerian Postal Service (NIPOST). Over the past few years, the advent of digital technology has significantly transformed the way the postal industry operates; this has disrupted traditional postal services, leading to a decline in demand for traditional postal services worldwide. Against this backdrop, this paper aimed at: determining the frequency of respondents` patronage of NIPOST`s services; examining the extent to which modern technologies have disrupted and impacted the traditional activities of NIPOST, and investigating the pace at which NIPOST has been adopting digital technologies. This study was anchored on the Diffusion of Innovations theory. The researchers employed a descriptive survey approach. The population of the study is the 1,100 Post Office box owners and operators in Ughelli, Delta State, Nigeria. A sample size of 285 was drawn from the population through the use of the Australian calculator for the determination of sample size. Questionnaire was utilised as the instrument for data collection. The findings revealed that respondents rarely patronise NIPOST`s for services. Also, findings indicated that NIPOST has been significantly affected by digital disruption, and that NIPOST has been slow in adopting digital technologies. Based on the findings of the study, it was recommended, among others, that Nigerians should massively patronise NIPOSTs services so as to keep the postal industry afloat. Likewise, NIPOST should speedily leverage digital innovations to enhance its operations and services, so as to improve customer satisfaction.